Can a familiar gender stereotype create a not-so-familiar benefit for women? Evidence of gendered differences in ascribed stereotypes and effects of team member adaptivity on performance evaluations - Carpini, J.A.; Luksyte, Aleksandra; Parker, Sharon; Collins, C.G. (2023)
Our research examines the differential effects of stereotypically feminine work behavior—team member adaptivity—on performance evaluations. Team member adaptivity requires being accommodating to changing relational and situational demands to achieve interdependent work goals. As such, women who engage in team member adaptivity will be recognized and rewarded more in their performance evaluations compared to men. We tested our model across three studies. As hypothesized, the results of Experimental Study 1 (N = 600) demonstrated team member adaptivity is subject to a gendered stereotype and ascribed to women more so than to men. Building on this finding, Field Study 2 (N = 96) demonstrated that team member adaptivity was positively related to performance evaluations for women but not for men. Study 3 used multi-source dyadic data obtained from managers and their supervisors (N = 141) and demonstrated that women who engage in team member adaptivity receive more favorable performance evaluations than their male counterparts. Together, these studies demonstrated the benefits of team member adaptivity for women more so than for men. This research extends our understanding of social role theory as well as the outcomes of adaptive performance while also offering several avenues for future scholarship with the potential to address ongoing gender inequities in the workplace.